Negative group delay devices : from concepts to applications - Ravelo, Blaise (The Institution of Engineering and Technology, 2018)
The book has 11 chapters dealing with the following topics: Microstrip line negative group delay circuits and applications to communication systems; Negative group delay power dividers; Delay-induced negative group delay; Microwave transversal and recursive filter-based negative group delay circuits and non-Foster elements; Hybrid coupler-based NGD circuit; NGD-based Hilbert filter; Design technique on the microwave amplifier-based active lumped NGD devices; Limits of passive and active negative group delay distributed circuits; Superluminality and detectable information in dispersive channels; Split-ring resonator-loaded X-band waveguide supporting negative group velocity; and Metamaterial-based common-mode noise filter with NGD effect for multilayer PCB.
Keywords: Electronic circuits.; Electric networks, Passive.; Junctions, Wave-guide.; Microwave amplifiers.; Microwave circuits.; Noise.; Printed circuits.; Resonators.; Wave guides.; elektronické knihy; electronic books